Exogenous ketone therapy for heart failure: A review - Yulia O. Aksenova; Yulia F. Osmolovskaya; Igor V. Zhirov; Allan G. Beniashvili; Margarita A. Morozova; Sergey N. Tereshchenko (ZAO "Consilium Medicum", 2023)
Heart failure is of major clinical and economic importance and remains a major public health problem worldwide. Despite existing treatment approaches, morbidity and mortality in these patients remains high. The progression of heart failure is accompanied by an increase in the metabolism of ketone bodies. The use of exogenous ketones may become a new therapeutic approach to increase cardiac efficiency, reduce energy deficit and improve cardiac function in patients with heart failure. The review presents the available data on ketone body metabolism in patients with heart failure, preclinical and clinical studies demonstrating the beneficial effects of exogenous ketone therapy in animal models and human studies with heart failure, and describes the potential pros and cons of using this therapeutic approach.